Mid-peripheral corneal steepening after orthokeratology - OUZZANI, Mhamed; Wright, Catherine Johanna; Sorbara, Luigina (Canadian Journal of Optometry, 2020)
Purpose: The purpose of this study was to retrospectively examine data from patients who had undergone orthokeratology (OK) to quantify the amount of mid-perpheral steeping in tangential curvature (MP-TC) and total refractive power (TRP) changes. Methods: Charts were reviewed from participants and data from the Pentacam instrument were collected prior to OK and after the final visit. Variables included central flattening (C-TC), the e-value, the mid-peripheral tangential curvatures (MP-TC), total corneal refractive power (TRP), the initial Rx (sphere) and initial corneal curvature (flat K). The group was further subdivided into high and low myopia for comparison. All participants were fitted with the Paragon CRT lenses. Data analysis was conducted to analyse the effects of lenses on TC and TRP. Results: A total of 40 patients (80 eyes) age13.95±6.80, 34 M and 46 F, were successfully fitted with CRT lenses. The average sphere was -4.23±0.90D for Group 1 and -1.89±0.62D for Group 2 The changes in TC and TRP from baseline were significant (both P<0.0001). The difference between the amount of C-TC and the maximum area of MPTC was ≈4.00D in the horizontal meridian and ≈3.00 in the veritcal meridian. The amount of MP-TC change from baseline was ≈2.00D in both meridians. There was a similar change in TRP: the distance from the centre to mid-periphery ≈2.50D. For C-TC, C-TRP, MP-TC, MP-TRP there was no significant difference between the 2 groups, overall (P=0.541 (TC) and P=0.321(TRP)). Conclusion: Results from this study should provide valuable insights into the topographic and refractive changes occurring with orthokeratology.